INOVASI METODE DAN MEDIA PEMBELAJARAN PAI DI SMP DARUL HIJRAH PUTRI MARTAPURA - Handayani, Nur Azmi Tri (FTIK UIN Sultan Aji Muhammad Idris Samarinda, 2025)
This community service activity aims to develop innovative interactive and contextual Islamic Religious Education (PAI) learning methods and media at Darul Hijrah Putri Martapura Middle School. Based on initial observations, it was found that the level of student enthusiasm in participating in PAI learning still varies, especially for certain materials. Contributing factors include fatigue due to busy activities outside the classroom and low interest in materials considered difficult. Through the Community Service Program (KKN), learning innovations based on educational games, creative LKPD (Student Work Unit), as well as role-playing activities and campaigns for Islamic values ​​were implemented. The results of the activity showed an increase in student enthusiasm, participation, and critical thinking skills. PAI teachers also gained new insights in the application of innovative technology-based methods and media, including the use of artificial intelligence (AI) in the preparation of In-Depth Learning Plans (RPM). This activity significantly contributes to improving the quality of PAI learning and strengthening collaboration between campuses and schools in building Islamic education that is adaptive to current developments.